Digital Transformation of Concrete Technology—A Review - Gamil, Yaser; Cwirzen, Andrzej (Frontiers in Built Environment, 2022)
Digital transformation of concrete technology is one of the current “hot topics” tackled by both academia and industry. The final goal is to fully integrate the already existing advanced concrete technologies with novel sensors, virtual reality, or internet of things. To create self-learning and highly automated platforms controlling design, production, and long-term usage and maintenance of concrete and concrete structures. The digital transformation should ultimately enhance sustainability, elongate service life as well as increase technological and cost efficiencies. This review article focuses on up-to-date developments. It explores current pathways and directions seen in research and industrial practices. It indicates benefits, challenges, and possible opportunities related to the digital transformation of concrete technology.